Taekwondo-In as a platform for the social integration of migrants - Jungjoo Yun; David Brown (Eracle. Journal of Sport and Social Sciences, 2025)
This article examines the phenomenon of social integration of migrants through the practice of the sporting and physical cultural activities. More specifically, it illustrates how Taekwondo, as a martial art and combat sport, can contribute to social integration. A collective instrumental case study gathered observational and interview data on three multicultural Taekwondo clubs. Following a directed content analysis, our findings suggest that Taekwondo can function as an effective platform for social integration promoting bridging, bonding forms of social capital and pluralised integrated identity as part of the development of a Taekwondo practitioner identity known as Taekwondo-In. In conclusion we consider the unique features these kinds of martial arts appear to have for functioning as platforms for social integration for both migrant and domestic populations, but that further research is needed including work to better understand the specific processes and practices through which arts like Taekwondo achieve this.